2011
DOI: 10.1002/hlca.201000365
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Leiocarpin C and (+)‐Goniodiol via an Olefin Cross‐Metathesis Protocol

Abstract: A stereoselective total synthesis of leiocarpin C (2) and (þ)-Goniodiol (1) by applying olefin crossmetathesis and substrate directed dihydroxylation as the key steps is reported (Scheme 3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 18 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Studies on three human cells lines, namely HL-60 (leukemia cells), HCT-8 (colon cancer cells) and MDA-MB-435 (melanoma cells) showed that leiocarpin is cytotoxic and its half-maximal inhibitory concentration (IC 50 ) values are 5.5, 6.9 and 13.7 µg/ml, respectively (Militão et al, 2007). Studies on understanding the synthesis of this compound have been reported (Yadav et al, 2008;Krishna and Alivelu, 2011).…”
Section: Pterocarpansmentioning
confidence: 99%
“…Studies on three human cells lines, namely HL-60 (leukemia cells), HCT-8 (colon cancer cells) and MDA-MB-435 (melanoma cells) showed that leiocarpin is cytotoxic and its half-maximal inhibitory concentration (IC 50 ) values are 5.5, 6.9 and 13.7 µg/ml, respectively (Militão et al, 2007). Studies on understanding the synthesis of this compound have been reported (Yadav et al, 2008;Krishna and Alivelu, 2011).…”
Section: Pterocarpansmentioning
confidence: 99%